Al- Radd al-jamil a fitting refutation of the divinity of Jesus : attributed to Abu Ḥamid al-Ghazali - Ġazzālī, Abū-Ḥāmid Muḥammad Ibn-Muḥammad al- 1058-1111 (History of Christian-Muslim relations, 2016)
Al-Radd al-jamil' attributed to al-Ghazali (d. 1111) is the most extensive and detailed refutation of the divinity of Jesus by a Muslim author in the classical period of Islam. Since the discovery of the manuscript in the 1930's scholars have debated whether the great Muslim theologian al-Ghazali was really the author. This is a new critical edition of the Arabic text and the first complete English translation. The introduction situates this work in the history of Muslim anti-Christian polemical writing. Mark Beaumont and Maha El Kaisy-Friemuth argue that this refutation comes from an admirer of al-Ghazali who sought to advance some of his key ideas for an Egyptian audience